Seasonally variable effects of spiders on herbivory and seed production of Chamaecrista neesiana (Leguminosae Caesalpinioideae). Issue 5 (2nd September 2020) - Silva, Ligia Aparecida; Vasconcellos-Neto, João; Del-Claro, Kleber; Stefani, Vanessa
Abstract : Spiders are diverse and abundant predators on vegetation in all terrestrial ecosystems, but only a few studies have examined their role in modulating spider–herbivore interactions throughout the year. We tested the hypothesis that spiders may reduce herbivore abundance on vegetation, resulting in lower leaf area loss and increased fitness (seed set production) of plants studied. In the tropics, this relationship will continue throughout the year. Our study was conducted in a cerrado environment in Brazil, using a shrub with glandular trichomes, Chamaecrista neesiana (Leguminosae Caesalpinioideae). We recorded phenological information, as well as the herbivorous insects and spiders present, on two groups of plants: a control group in which spiders were present and an experimental group in which spiders were removed. The results indicated that spiders had a positive indirect effect on plants by reducing leaf area loss and increasing seed set production, confirming our hypothesis. The benefits were higher in the rainy season, coinciding with the peak abundance of the spider species Peucetia flava . Our results indicate that protection against herbivory by spiders in the tropical savanna is conditional on the abundance of predators over time.